Simulation Model of the Artificial Lung Ventilation Apparatus - P. V. Kamlach; M. I. Kuprianau; V. M. Bandarik; D. V. Likhacheuski; A. V. Slizhova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
A model for the flow of a gas mixture in the respiratory circuit of an artificial lung ventilation apparatus has been developed. This model can be used to calculate the optimal values for artificial lung ventilation. It can also be used to simulate various situations that may arise during the treatment of a patient. In this paper, the cases were considered when the tubes were straight and when they were subjected to physical pressure, as well as when the tubes were subjected to a change in geometry (bent). The values of excess pressure in the respiratory circuit of the artificial lung ventilation apparatus were calculated. Recommendations on the use of the model are given.